Embedding a primary care provider in sickle cell teams improves sickle cell care - Sherraine Della-Moretta; Rina Li Welkie; Nives Quaye; Kristina Landes; Regina D. Crawford; Payal Desai; Robert M. Cronin (PLoS ONE, 2026)
Adults with sickle cell disease (SCD) experience fragmented access to primary and preventive care, which leads to poor adherence to general and SCD‑specific clinical practice guidelines. To address this gap, we implemented an embedded primary care model where a board‑certified internist/pediatric primary care provider (PCP) was embedded as a full member of the adult SCD care team, attending operational and educational meetings and practicing alongside hematologists in a comprehensive SCD clinic. Our primary aim was to test the hypothesis that an embedded primary care model was associated with improved guideline‑based preventive care and changes in acute healthcare utilization (e.g., emergency room visits and hospitalizations). We conducted a retrospective cohort study of adults with SCD seen at a single tertiary care center between July 2020 and June 2025. Of the 388 adults with SCD seen at the center, 174 received care from the embedded PCP. Patients in the embedded PCP model demonstrated significantly higher adherence to general preventive care including cervical cancer screening ((Odds Ratio) OR: 4.49; 95% (Confidence Interval) CI: 2.46, 8.23), depression screening (OR: 7.97; 95% CI: 1.78, 35.69), and diphtheria-tetanus-pertussis (Tdap) immunization (OR: 2.88; 95% CI:1.72, 4.84), and SCD‑specific guidelines, including annual eye examinations (OR: 2.59; 95% CI: 1.66, 4.04), pneumococcal immunization (OR: 3.58; 95% CI: 2.16, 5.92), urine protein screening (OR: 3.36; 95% CI: 1.89, 6.00), and ACE inhibitor/ARB use for microalbuminuria (OR: 9.37; 95% CI: 3.11, 28.23). Among patients who saw the embedded PCP, patients had significantly more annual outpatient visits (post-PCP: 4.2 vs pre-PCP: 2.7, p < 0.0001) and, while insignificant, fewer annual inpatient admissions (post-PCP: 1.4 vs pre-PCP: 1.9, p = 0.4869). Embedding a PCP within the adult SCD care team was associated with improved guideline‑based preventive care and more annual outpatient visits, which was consistent with more coordinated, outpatient‑focused management.